Corporate Social Responsibility Disclosure, Corporate Governance Disclosures, and Firm Value In Indonesia Chemical, Plastic, and Packaging Sub-Sector Companies - Firmansyah, Amrie; Husna, Mitsalina Choirun; Putri, Maritsa Agasta (Universitas Negeri Semarang, 2021)
This study aims to examine environmental disclosure, social disclosure, economic disclosure, and corporate governance disclosures on the firm value in Indonesia. This study uses a quantitative method with multiple regression. This study employs data from chemical, plastic, and packaging sub-sector companies which listed in the IDX. After purposive sampling was conducted, the final sample consists of eleven companies from 2016 up to 2019. The result suggests that environmental disclosure positively affects firm value. Meanwhile, economic and social disclosures do not affect firm value. Also, the disclosure of corporate governance does not affect firm value. The companies should consider that environmental activities as a strategy for the company, and these activities show that the company's success in the capital market is related to investors' positive response. Keywords: Corporate Governance, Economic, Environmental, Social, Disclosure